PENGARUH PENGGUNAAN FACEBOOK BAGI KEHIDUPAN ROHANI MAHASISWA STKIP WIDYA YUWANA - Anastasia Dwilestari; Agustinus Wisnu Dewantara (Lembaga Penelitian STKIP Widya Yuwana, 2019)
The church is always determined to serve the people of its time, and also to keep abreast of the times with its ways. The development of the technological age that is seen, one of them is the internet that provides various kinds of social networks. Facebook is one of the social networks used in everyday life and influences the user. Based on the background above, the researcher can formulate a number of problem formulations as follows: What is meant by Facebook? What is meant by spiritual life? What is the influence using of Facebook on the spiritual life of students in STKIP Widya Yuwana Madiun? This study aims to describe the meaning of Facebook; describe the meaning of spiritual life, describe the influence using of Facebook on spiritual life of students in STKIP Widya Yuwana. This study used a qualitative method by collecting data through interviews with 8 respondents. Qualitative research is an open interview as an effort to examine and understand the attitudes, views, feelings and behavior of individuals or groups of people on a problem. Qualitative methods are as a form of research that is more focused on efforts to see, understand attitudes, feelings, views and behaviors both individually and in groups regarding an event.